Performing arts and gender in postcolonial western Uganda - Cimardi, Linda (Eastman/Rochester studies in ethnomusicology ;, 2023)
"Drawing on archival research and extensive fieldwork in the regions of Bunyoro and Tooro, Linda Cimardi examines the connection between traditional performing arts and gender in Western Uganda. The book focuses on runyege, the main genre of the Banyoro and Batooro people, exploring its different components of singing, instrument playing, dancing, and acting and identifying their complex relationships to gender models and expressions. Today mainly performed at Ugandan school festivals and by semiprofessional ensembles, repertoires like runyege adhere to stage conventions that have developed over several decades. Some of these conventions are powerful devices allowing the actors involved (performers, teachers, students, adjudicators, and audiences) to collectively shape an image of local culture grounded in a gender notion that is perceived as traditional. At the same time, stage conventions are exploited by some performers to negotiate their gender identities and expressions in unconventional ways, thus challenging hegemonic gender models. Examining traditional arts as both the manifestation and the building blocks of local culture, the book vibrantly depicts the imbrication of Ugandan performing arts with gender and postcolonialism"--